Coordination of care in health systems for users with diabetes and hypertension: a scoping review - Virgílio Luiz Marques de Macedo; Naira Pereira de Sousa; Ana Cristina dos Santos; Walterlânia Santos; Marina Morato Stival; Tânia Cristina Morais Santa Barbara Rehem (Revista Latino-Americana de Enfermagem)
Objective: to map the available evidence on the characteristics of care coordination between Primary Health Care and Specialized Outpatient Care for users with diabetes and hypertension. Method: this is a scoping review with 40 articles as the final sample, evaluated by means of Content Analysis, of the thematic-categorical type, with the aid of a technological tool. Results: care coordination was defined by means of eight categories: information and communication, integration of care, improvement and quality, care management, care sharing, fundamental attribute, health professionals and health service users, with the results of the articles concentrating mainly on four categories, with information and communication standing out, followed by the category of care management and the category of care sharing, in parallel with improvement and quality. Conclusion: technological tools are a first step in ensuring the coordination of care, proving to be a significant feature, with emphasis on studies on the sharing of information between health services through electronic medical records. However, although this technology has proved to be advantageous for the health system, with good results, it is not the only means of ensuring the coordination of care.